Influenza-Associated Parotitis During the 2014–2015 Influenza Season in the United States. (30th March 2018) - Rolfes, Melissa A; Millman, Alexander J; Talley, Pamela; Elbadawi, Lina I; Kramer, Natalie A; Barnes, John R; Blanton, Lenee; Davis, Jeffrey P; Cole, Stefanie; Dreisig, John J; Garten, Rebecca; Haupt, Thomas; et al.
Abstract : We report a large number of patients with influenza-associated parotitis during the 2014–2015 US influenza season. Because of different control measures for mumps and influenza, we recommend influenza be considered among patients with acute parotitis during the influenza season. Abstract: Background: During the 2014–2015 influenza season in the United States, 256 cases of influenza-associated parotitis were reported from 27 states. We conducted a case-control study and laboratory investigation to further describe this rare clinical manifestation of influenza. Methods: During February 2015–April 2015, we interviewed 50 cases (with parotitis) and 124 ill controls (without parotitis) with laboratory-confirmed influenza; participants resided in 11 states and were matched by age, state, hospital admission status, and specimen collection date. Influenza viruses were characterized using real-time polymerase chain reaction and next-generation sequencing. We compared cases and controls using conditional logistic regression. Specimens from additional reported cases were also analyzed. Results: Cases, 73% of whom were aged <20 years, experienced painful (86%), unilateral (68%) parotitis a median of 4 (range, 0–16) days after onset of systemic or respiratory symptoms. Cases were more likely than controls to be male (76% vs 51%; P = .005). We detected influenza A(H3N2) viruses, genetic group 3C.2a, in 100% (32/32) of case and 92% (105/108) of control specimens sequenced ( P = .22). Influenza B and A(H3N2) 3C.3 and 3C.3b genetic group virus infections were detected in specimens from additional cases. Conclusions: Influenza-associated parotitis, as reported here and in prior sporadic case reports, seems to occur primarily with influenza A(H3N2) virus infection. Because of the different clinical and infection control considerations for mumps and influenza virus infections, we recommend clinicians consider influenza in the differential diagnoses among patients with acute parotitis during the influenza season.